Peningkatan Minat Bersekolah di SMP IT Buahati Melalui Penguatan Price Value, Word of Mouth dan Brand Image - Amin Zakiwintoro (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyse the influence of Price Value and Word of Mouth on School Enrollment Interest with Brand Image as a mediating variable at SMPIT Buahati. The research employed a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The sample consisted of 108 respondents who were prospective students' parents. The results indicate that Price Value, Word of Mouth, and Brand Image have a positive and significant influence on School Enrollment Interest. Brand Image is also proven to significantly mediate the relationship between Price Value and Word of Mouth on School Enrollment Interest. These findings highlight the importance of appropriate price perception, positive testimonials from others, and a strong school image in attracting parents to enrol their children. The practical implications of this study suggest the need for communication strategies that emphasise the excellence of educational services relative to cost, strengthening the parent community as WOM agents, and continuous efforts to build and maintain a positive school image.